Echographic approaches to diagnosing and evaluating obstructive uropathies in pregnant women. Case report - Sergey M. Voevodin; Akif A. Yusufov; Tatiana V. Shemanaeva (IP Berlin A.V., 2024)
Obstructive uropathy (OU) is a complication of urinary tract diseases, characterized by the presence of an obstacle in the urine outflow. This condition in pregnant women usually leads to urological and/or obstetric complications and requires timely diagnosis to optimize the treatment. A description of the ultrasound findings and a review of two cases of OU in pregnant women are presented. The indication for an ultrasound examination of the kidneys was clinical and laboratory findings. The identified signs and features of the OU became the basis for appropriate treatment and prevention of severe obstetric complications, which were avoided in our cases. However, the outcomes of the described clinical cases indicate the need for a more thorough urological and obstetric approach to women with obstruction uropathy. The ultrasound examination to detect obstructive uropathy in pregnant women, as well as the details and determination of possible etiological factors, were a reliable means of preventing severe obstetric and perinatal complications.